Practices and Techniques of School Heads of Region IV-A (CALABARZON) in Influencing People: Towards School Leader Program/Course Design - Panganiban, A C (KnE Social Sciences, 2018)
This paper aimed to determine the practices and techniques used by the school heads in influencing their school personnel.The researcher used the descriptive method of research. The descriptive research design was partnered with correlational survey which is a method determines the relationship between two variables.Majority of the school heads in the CALABARZON region possess graduate level acuity and orientation that would one way or another may contribute and aid them in their supervision and administrative functions. The seminars and trainings oriented them and equipped them with the needed and appropriate knowledge, techniques, and practices in influencing people. The School heads of the CALABARZON region public schools are very much knowledgeable and aware of the practices and techniques neede to influence their personnel in achieving goals and task. Keywords: Influence, School heads, Management Influence, Management Persuasion